Is Onlay Polypropylene Mesh Repair an Available Option for Incisional Hernia Repair? A Retrospective Cohort Study. Issue 2 (February 2019) - Cano-Valderrama, Oscar; Porrero, JosÉ L.; Quirós, Esther; Bonachia, Oscar; Castillo, MarÍA J.; Cervantes, Norman; Marcos, Alberto; Torres, Antonio J.
Lately, incisional hernia repair (IHR) with onlay polypropylene mesh has been replaced by other surgical procedures. The aim of this study was to compare the complication and recurrence rate after onlay mesh repair and other surgical procedures for IHR. A retrospective cohort study of patients who underwent IHR in a single center was conducted. The data were obtained from electronic medical records. Patients who had been lost during follow-up were contacted for a visit in the clinic. Univariate and multivariate analysis was performed with Stata 13.0 to analyze the factors associated with postoperative complications and hernia recurrence. Between June 2004 and December 2015, 1078 patients underwent IHR in a single center. Onlay mesh repair was performed in 125 patients (11.6%). Other surgical procedures included Rives procedure (29.3%), sublay mesh repair (38.6%), intrabdominal mesh repair (17.1%), and primary closure (3.4%). After a mean follow-up of 2.8 years, 73 (7%) patients developed a recurrence. A higher percentage of complications were seen after onlay mesh repair than after other surgical procedures (22.4% vs 13.1%, P = 0.005). Nevertheless, recurrence was less frequent after onlay mesh repair (4.2% vs 7.1%, P = 0.241). Logistic regression discarded an association between onlay mesh repair and hernia recurrence or postoperative complications. Incisional hernia repair with onlay polypropylene mesh repair was not associated with a higher incidence of postoperative complications or recurrence rate. So, this procedure should not be discarded in selected patients presenting with incisional hernia.